2018
DOI: 10.3749/canmin.1700038
|View full text |Cite
|
Sign up to set email alerts
|

REE Redistribution Textures in Altered Fluorapatite: Symplectites, Veins, and Phosphate-Silicate-Carbonate Assemblages from the Nolans Bore P-REE-Th Deposit, Northern Territory, Australia

Abstract: The geochemical behavior and genesis of rare earth element (REE) ores remains poorly understood. In addition, the processes responsible for many features observed in REE ore deposits are not easily determined. Importantly, the distinction between igneous versus post-magmatic genesis, or the nature of the mineralizing and modifying fluids or melts, remains in dispute. Nolans Bore is a P-REE-Th deposit in the Northern Territory, Australia, hosting REE mineralization in fluorapatite and its alteration products. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 142 publications
(193 reference statements)
1
21
0
Order By: Relevance
“…Presumably, thorite or huttonite (complementary to monazite) is the product of the selective concentration of elements (Th and HREE) released during apatite decomposition. A similar selective redistribution of LREE and Th-HREE has been described in carbonatites of Nolans Bore (Australia) [8].…”
Section: Late-stage Processessupporting
confidence: 75%
See 1 more Smart Citation
“…Presumably, thorite or huttonite (complementary to monazite) is the product of the selective concentration of elements (Th and HREE) released during apatite decomposition. A similar selective redistribution of LREE and Th-HREE has been described in carbonatites of Nolans Bore (Australia) [8].…”
Section: Late-stage Processessupporting
confidence: 75%
“…Therefore, rare earth carbonatites are a major focus of critical metal research. Over the past five years, several dozens of papers have been published on the subject of rare earth carbonatites (RE carbonatites) in Angola [5,6], Australia [7][8][9], Brazil [10,11], Canada [12][13][14][15][16][17], China [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], Finland [38], India [39][40][41][42], Italy [43,44], Malawi [45][46][47][48][49][50][51], Mongolia [52,53], Namibia…”
Section: Introductionmentioning
confidence: 99%
“…However, previous experimental results have indicated that apatite could be altered or metasomatized by moderate to high‐temperature (300 to 900°C) fluids, such as H 2 O‐CO 2 fluids, acidic and alkalic fluids (Betkowski et al, ; Harlov & Förster, ; Harlov et al, ; Migdisov & Williams‐Jones, ; Migdisov et al, ). Altered apatite, with significant variations in elemental content, is widely reported in rocks affacted by moderate to high‐temperature (>300°C) hydrothermal fluids, especially in mineral deposits (Anenburg et al, ; Bouzari et al, ; Li et al, ; Li & Zhou, ; Palma et al, ; Zeng et al, ). In addition, modifications of the Sr, Nd, and O isotopic systems in apatite have been reported in mineralized rocks that have been altered by moderate to high‐temperature hydrothermal fluids (Li et al, ; Zeng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although REE are generally considered immobile in most natural systems, the occurrence of REE-rich minerals of unmistakably hydrothermal genesis attests to their mobility (8). In addition, P and F are considered to immobilize REE in hydrothermal systems (39)(40)(41)(43)(44)(45). However, many carbonatite-associated hydrothermal veins contain P-and F-bearing minerals such as fluorapatite, monazite, xenotime, and REE fluorcarbonates (39,41), indicating that REE, P, and F were enigmatically transported together.…”
Section: Complexing Ligands and Fractionation Of Hree From Lreementioning
confidence: 99%